2002
DOI: 10.1212/wnl.58.9.1395
|View full text |Cite
|
Sign up to set email alerts
|

Functional vitamin B 12 deficiency and Alzheimer disease

Abstract: Moderately elevated total serum homocysteine is associated with an increased risk of atherothrombotic vascular events. Accordingly, serum homocysteine is increased in patients with vascular dementia but is also increased in clinically diagnosed and histologically confirmed AD. It is generally considered that homocysteine potentiates endothelial and neuronal oxidative injury in these diseases. A complementary model of oxidative stress-induced hyperhomocystinemia is proposed by the authors. The hypothesis accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 29 publications
4
121
0
3
Order By: Relevance
“…Sepsis-induced inhibition of these methyltransferases may lead to impaired SAM utilization and contribute to the increase in SAM levels. Increased Hcy remethylation to methionine and finally SAM during sepsis is unlikely, as oxidative stress leads to lower methionine synthase and betaine-Hcy S-methyltransferase activity (19)(20)(21). In addition, we would expect Hcy levels to be lower in septic animals if increased remethylation occurred during sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis-induced inhibition of these methyltransferases may lead to impaired SAM utilization and contribute to the increase in SAM levels. Increased Hcy remethylation to methionine and finally SAM during sepsis is unlikely, as oxidative stress leads to lower methionine synthase and betaine-Hcy S-methyltransferase activity (19)(20)(21). In addition, we would expect Hcy levels to be lower in septic animals if increased remethylation occurred during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results indicate that higher levels of SAM lead to a higher transsulfuration rate to allow GSX synthesis for defense of oxidative stress induced by sepsis. In addition, oxidative stress leads to an increased Hcy flux through the transsulfuration pathway by up-regulation of CBS activity (35) and decreased activity of methionine synthase and betaine-Hcy S-methyltransferase (19)(20)(21). Increased transsulfuration rates during experimentally induced sepsis were also shown by injection of radiolabeled cysteine and methionine in rats (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, McCaddon and coworkers suggested that GSCbl and related thiolatocobalamins might be more effective than currently available pharmaceutical B 12 forms (CNCbl and H 2 OCbl + ) in treating B 12 -related conditions associated with oxidative stress such as Alzheimer's disease. 34,35 However, the apparent clinical benefit of combining N-acetyl-L-cysteine with H 2 OCbl + in patients with Alzheimer's disease or mild cognitive impairment requires formal clinical trials to prove or refute such observations. 34,46 In this paper we describe the synthesis of three novel thiolatocobalamins: D,Lhomocysteinylcobalamin (HcyCbl), the sodium salt of N-acetyl-L-cysteinylcobalamin (Na [NACCbl]), and 2-N-acetylamino-2-carbomethoxy-L-ethanethiolatocobalamin (NACMECbl).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 However, the apparent clinical benefit of combining N-acetyl-L-cysteine with H 2 OCbl + in patients with Alzheimer's disease or mild cognitive impairment requires formal clinical trials to prove or refute such observations. 34,46 In this paper we describe the synthesis of three novel thiolatocobalamins: D,Lhomocysteinylcobalamin (HcyCbl), the sodium salt of N-acetyl-L-cysteinylcobalamin (Na [NACCbl]), and 2-N-acetylamino-2-carbomethoxy-L-ethanethiolatocobalamin (NACMECbl). The thiol ligand structures are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation